Effects of emotion and semantic relatedness on recognition memory: Behavioral and electrophysiological evidence. (22nd July 2022) - Han, Meng; Li, Bingcan; Guo, Chunyan; Tibon, Roni
Abstract: Some aspects of our memory are enhanced by emotion, whereas others can be unaffected or even hindered. Previous studies reported impaired associative memory of emotional content, an effect termed associative "emotional interference". The current study used EEG and an associative recognition paradigm to investigate the cognitive and neural mechanisms associated with this effect. In two experiments, participants studied negative and neutral stimulus‐pairs that were either semantically related or unrelated. In Experiment 1 emotions were relevant to the encoding task (valence judgment) whereas in Experiment 2 emotions were irrelevant (familiarity judgment). In a subsequent associative recognition test, EEG was recorded while participants discriminated between intact, rearranged, and new pairs. An associative emotional interference effect was observed in both experiments, but was attenuated for semantically related pairs in Experiment 1, where valence was relevant to the task. Moreover, a modulation of an early associative memory ERP component (300–550 ms) occurred for negative pairs when valence was task‐relevant (Experiment 1), but for semantically related pairs when valence was irrelevant (Experiment 2). A later ERP component (550–800 ms) showed a more general pattern, and was observed in all experimental conditions. These results suggest that both valence and semantic relations can act as an organizing principle that promotes associative binding. Their ability to contribute to successful retrieval depends on specific task demands. Abstract : Although research has reported impaired associative memory of emotional content ("associative interference"), it had been shown that this effect is sometimes attenuated. Nevertheless, the cognitive and neural mechanisms that support this attenuation remain unclear. We show here that when emotions are task‐relevant, negative valence can act as an organizing principle that promotes associative binding via increased availability of familiarity‐based retrieval, thereby attenuating the emotional associative interference effect.